Obtenção de gorduras poli-insaturadas atraves do óleo de vísceras de Tilápia do Nilo (Oreocrhomis Niloticus, L.) e sementes de oiticica pelo método de complexação com ureia - Lemos, Dármia Maria Mendes (2015)
Tilapia of the Nile (Oreochromis niloticus) is a freshwater fish that for its ease of adaptation and great taste is becoming one of the most consumed fish in the world, however, its production chain generates various organic waste as guts, fins, heads They need a proper disposal because this material rich in lipids was thrown to the banks of rivers, ponds or on the ground can contaminate the water table bringing a serious environmental damage. The market is every day looking for different and even unique products, thus arises the market for polyunsaturated fats. The objective was to seize the oil viscera of Nile Tilapia (Oreochromis niloticus) in getting polyunsaturated fats through complexation method with urea. Processing took place at Padetec located at the Federal University of Ceará UFC, where the oil was extracted by the viscera hot indirect method. The crude oil obtained and the degummed oil, neutralized and clarified were characterized on the following parameters, Acid Value, free fatty acids, peroxide index, iodine and saponification Index. It also assessed the performance and stability of the viscera for oil extraction. A crude oil sample and a refined oil underwent complexing with urea to be taken posteriorrmente gas chromatography. Complexing the following conditions were applied: triglyceride ratio urea / 1: 7, reaction temperature: 20 ° C and time of 10 hours reaction. Statistical analysis of the crude oil was applied parameters, degummed, neutralized, bleached / clarified, was used analysis of variance (ANOVA). The yield results were always in the range of 50%, since the stability of oil extracted from the offal at different times showed a gradual increase every time, even with freezing. The results of physicochemical tests showed results with little variation in all refining steps: Crude oil, degummed, neutralized and bleached / clarified, reminding of the importance of freezing the viscera and fast processing of the same. It was concluded that the use of Nile Tilapia viscera (Oreochromis niloticus) proved to be a viable alternative due to satisfactory results in performance evaluation, stability and physicochemical characteristics, requiring just a process aimed at maintaining the quality of the viscera until the moment of extraction of oils to obtain a product with good nutritional and sensory quality.